Raising the bar (18). Issue 4 (2nd October 2021) - Elhorst, Paul; Abreu, Maria; Amaral, Pedro; Bhattacharjee, Arnab; Chasco, Coro; Corrado, Luisa; Ditzen, Jan; Doran, Justin; Felsenstein, Daniel; Fuerst, Franz; Le Gallo, Julie; McCann, Philip; et al.
ABSTRACT: This editorial summarizes the papers published in issue 16(4) (2021). The first paper adopts a higher order spatial autoregressive model with endogenous spatial weight matrices. The second paper investigates the existence of the law of one price using regional observations over time. The third paper develops an economic-theoretical model that goes against the common belief that the most productive individuals and firms agglomerate at the core. The fourth paper provides empirical evidence that merger and acquisition deals are more likely to occur between firms in culturally than in geographically contiguous countries. The fifth paper develops a spatial econometric estimator based on the indirect inference principle. The sixth paper examines the investment behaviour of First Nation governments through joint ventures. The seventh paper employs a spatial econometric model with an endogenous spatial weight matrix to construct intraregional input-output models.